The industrialisation of cyber extortion. Issue 12 (December 2021) - Buckley, Joseph
Abstract : Ransomware extortion continues to be the key cyberthreat to organisations globally. Organisations' increasing reliance on digital services and interconnected business, and on both IT and operational systems, has led to the rising profitability of cybercrime and ever more advanced cyber criminal tactics.